Analisis Peran Guru dalam Aktivitas Membaca 10 Menit Terhadap Keterampilan Membaca Pemahaman Kelas III SDN Banyuajuh 02 - Saherna, Mutiara Navy Putri; Harsiwi, Nova Estu (Indo-MathEdu Intellectuals Journal, 2025)
The aim of this research is to know the role that teachers apply in the 10-minute reading activity so that third-grade students at Banyuajuh 02 Elementary School have a good understanding of the reading material. This research uses qualitative descriptive methods. This research was conducted at UPTD Banyuajuh 02 Elementary School in Kamal. The subjects of this research are third-grade teachers who have direct responsibility for implementing the reading program in their classes. The results of this research were obtained through various data collection techniques, namely interviews, observations, and documentation. The data analysis technique used is qualitative data analysis, which consists of data reduction, data presentation, and conclusion drawing. The validity test for the data in this study uses source and technique triangulation. The research results show that the roles played by teachers in students' reading interest are as follows: the teacher as an educator, the teacher as a guide, and the teacher as an individual. The indicators of the teacher's role as an educator meet three sub-indicators, namely easy-to-understand delivery, answering students' questions, and a conducive atmosphere. Then, the teacher as a guide meets three sub-indicators, which are providing guidance, encouraging students to ask questions, and translating difficult words. Finally, the teacher as an individual meets one sub-indicator, which is the teacher's attitude during activities